2011
DOI: 10.1175/mwr-d-11-00006.1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations of Warm-Season Precipitation East of the Tibetan Plateau over China

Abstract: This study explores the diurnal variations of the warm-season precipitation to the east of the Tibetan Plateau over China using the high-resolution NOAA/Climate Prediction Center morphing technique (CMORPH) precipitation data and the Global Forecast System (GFS) gridded analyses during mid-May to mid-August of 2003-09. Complementary to the past studies using satellite or surface observations, it is found that there are strong diurnal variations in the summertime precipitation over the focus domain to the east … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
139
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 40 publications
(54 reference statements)
12
139
0
Order By: Relevance
“…The time step is set to 30 s. As is known to meteorologists around the world, it is very difficult to obtain an accurate track and rainfall simulation for a 10-day TD through continuous model integration, despite some successful studies that have conducted long-time numerical simulations to investigate the diurnal rainfall cycle [9,26]. Considering the fact that the observed features of the diurnal rainfall cycle are obtained by averaging hourly TRMM-estimated or surface rain-gauge rainfall [8,13,45], an alternative method is adopted in this study. Ten simulations have been done in this study to cover the 10-day period of the case, with each simulation being initialized at 2000 BLT (1200 UTC) and integrated for 36 h. The last 24-h results are used for analysis, while the first 12-h results are discarded to alleviate the model spin-up impacts.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The time step is set to 30 s. As is known to meteorologists around the world, it is very difficult to obtain an accurate track and rainfall simulation for a 10-day TD through continuous model integration, despite some successful studies that have conducted long-time numerical simulations to investigate the diurnal rainfall cycle [9,26]. Considering the fact that the observed features of the diurnal rainfall cycle are obtained by averaging hourly TRMM-estimated or surface rain-gauge rainfall [8,13,45], an alternative method is adopted in this study. Ten simulations have been done in this study to cover the 10-day period of the case, with each simulation being initialized at 2000 BLT (1200 UTC) and integrated for 36 h. The last 24-h results are used for analysis, while the first 12-h results are discarded to alleviate the model spin-up impacts.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 99%
“…Regional and/or seasonal differences of diurnal rainfall patterns not only occur in China [8,[18][19][20], but also exist in other regions of the world, like in Japan [21], island regions in Asia [22,23], the Asian monsoon region [10][11][12], marine continental islands [24,25], northwest South America [26], the United States Great Plains [27], the Andes in South America [28,29], Africa [30] and even the global tropics [31,32]. The convective rainfall maximum late at night or in the early-morning hours over oceans can be explained by radiation-convection interaction theory [33,34].…”
mentioning
confidence: 99%
“…The nocturnal precipitation in the Sichuan Basin in summer, i.e. the precipitation reaches its diurnal peak around midnight, becomes a hot topic in the recent decade (Li et al 2008;Yu et al 2007aYu et al , 2009Chen et al 2010;Huang et al 2010;Bao et al 2011;Yuan et al 2011). This phenomenon has been observed and documented since long time (Lu 1942;Ye and Gao 1979;Zeng et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2007b) and Li et al (2008) showed that the summertime nocturnal precipitation in the Sichuan Basin is contributed mainly by long-duration precipitating systems. In addition, the diurnal cycle of precipitation presents an eastward delayed diurnal phase from the east of the Tibetan Plateau (TP) down to the Yangtze River valley in central China Huang et al 2010;Bao et al 2011;Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation